Synthesis and Characterization of Natural Hydroxyapatite (Hap) from Black Sumatraand Gallus Domesticus Bone for Orthopedic Applications - Kumar.D, Ajith; Abinesh. S, Salan; . E, Kannan; Priya.N, Siva (International Journal of Psychosocial Rehabilitation, 2020)
Biomaterial substances are widely used in the biological system. Different physical, chemical and natural methods are used to biomaterials are synthesized. This present work focused on biomaterials selected from different two rare species of chicken (Black Sumatra and Gallus Domestics) bone. The thermal calcination method used for the natural hydroxyapatite (HAP) was isolated from the Black Sumatra and Gallus Domestics chicken bones. The isolated hydroxyapatite (HAP) has been characterized using X-ray diffraction analysis (XRD), Fourier transformed infrared (FTIR), and scanning electron microscopy (SEM). After characterization, this material is applicable for bone cement, bone implantation, bone stabilization, and bone injury.